2016
DOI: 10.1371/journal.pntd.0005217
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Distribution and Clearance of Purified Capsular Polysaccharide from Burkholderia pseudomallei in a Murine Model

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, a severe infection prominent in northern Australia and Southeast Asia. The “gold standard” for melioidosis diagnosis is bacterial isolation, which takes several days to complete. The resulting delay in diagnosis leads to delayed treatments, which could result in death. In an attempt to develop better methods for early diagnosis of melioidosis, B. pseudomallei capsular polysaccharide (CPS) was identified as an important diagnostic biomarker. A rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Cross reactivity with purified CPSI suggested that the acidic exopolysaccharide-specific antibody reacts with a constituent of CPSI ( Fig 7A ). We also confirmed that the polysaccharide preparations produced by the becA-R biosynthetic cluster were not CPSI ( Fig 7B ), since the purified CPSI [ 14 ] and preparations from Δ becA-R are reactive to the CPSI-specific 4C4 IgG1 antibody [ 46 , 60 , 61 ], whereas the preparations from Δ wcbR-A mutant and the Δ wcbR-A Δ becA-R double mutants are not reactive to the CPSI-specific 4C4 IgG1 antibody.…”
Section: Resultssupporting
confidence: 66%
“…Cross reactivity with purified CPSI suggested that the acidic exopolysaccharide-specific antibody reacts with a constituent of CPSI ( Fig 7A ). We also confirmed that the polysaccharide preparations produced by the becA-R biosynthetic cluster were not CPSI ( Fig 7B ), since the purified CPSI [ 14 ] and preparations from Δ becA-R are reactive to the CPSI-specific 4C4 IgG1 antibody [ 46 , 60 , 61 ], whereas the preparations from Δ wcbR-A mutant and the Δ wcbR-A Δ becA-R double mutants are not reactive to the CPSI-specific 4C4 IgG1 antibody.…”
Section: Resultssupporting
confidence: 66%
“…The polysaccharide antigen detected by the AMD has been shown to be largely eliminated by renal filtration in a murine model, forming a single-walled nanotube structure that may allow its filtration through the glomerulus despite its high molecular weight of 300 kDa 33 . Thus, even when viable B. pseudomallei are not present in urine, antigenuria might result in a positive AMD.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the accuracy of the AMD lateral flow immunoassay (LFI) for the rapid diagnosis of melioidosis directly from clinical samples. The LFI detects an extracellular polysaccharide of B. pseudomallei with a limit of detection (LOD) of 0.2 ng/ml ( 13 , 21 ). On turbid blood cultures, the AMD was found to have excellent analytical and diagnostic sensitivity and specificity, comparable to those of both IFA and latex agglutination, which were found to have performance characteristics similar to those published in previous studies ( 11 , 17 , 18 , 22 ).…”
Section: Discussionmentioning
confidence: 99%